Activity of Educational Museums of Prykarpattia (ХХ – ХХІ Century) - Inna Strazhnikova (Pedagogical Discourse, 2015)
Interpretation of the concept «museum pedagogics» is examined in the article, as an area of knowledge and form of collective studies and education, claim of the ideas of the differentiated approach to the different categories of visitors; application in many museums of the various interactive programs for visitors; quantitative correlation of the passport system of museums is shown.